Czech-ing Shakespeare: Tracing Shakespeare’s Influence (not only) in Czech Advertisements - Mišterová, Ivona (American & British Studies Annual, 2024)
Shakespeare’s plays are indisputably among the most translated, staged, and adapted works for both theatre and screen. The texts undergo updating, recontextualization, and transcultural adaptation to engage audiences across different age groups, thereby facilitating their reception. This article explores Shakespeare’s position in modern popular culture. Initially, Shakespeare’s status in popular culture is discussed, drawing on the concepts of Graham Holderness (1988), Douglas Lanier (2002, 2006), and Marjorie Garber (2008). The article then examines selected popular Shakespearean representations, such as Richard Burt’s concept of “Schlockspeare” (2002), which focuses on the use of catchphrases, references, along with both textual and visual allusions to Shakespeare in advertising (e.g. mortgage loans from Commercial Bank, a Shakespeare-inspired yogurt, etc.). The objective is to demonstrate that popular culture serves to disseminate Shakespeare’s work without diminishing its inherent value, echoing Graham Holderness’s assertion that Shakespeare is, here, now, always, what is currently being made of him.”